The Effect of Entrepreneurship Education and Sociological on Student's Entrepreneurial Intention : The Perspective of Entrepreneurial Skills Theory and Social Capital Theory - D Yadi Heryadi; Amruddin Amruddin; Jonni Mardizal; Syamsuri Syamsuri; Loso Judijanto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to analyze the effect of entrepreneurship education and sociological factors on the entrepreneurial intentions of students. Two theories integrated into this research were the Entrepreneurial Skills Theory and Social Capital Theory. The research adopts a quantitative approach, applying structural equation modeling (SEM) and Partial Least Square (PLS) for analysis. The non-probability sampling technique used was Purposive Sampling to determine the research sample. The study participants consisted of 68 college students in Tasikmalaya, Indonesia, selected to complete an online questionnaire. The research findings indicated that entrepreneurship education and sociological factors significantly and positively influence students' entrepreneurial intentions. Furthermore, both the Entrepreneurial Skills Theory and Social Capital Theory not only have individual positive impacts but also complement each other in shaping students' entrepreneurial intentions. The integration of entrepreneurship education, combining the development of individual skills with the strengthening of social relationships and collaboration, was an effective foundation for motivating and preparing students to face challenges in the business world.